Myelin oligodendrocyte glycoprotein (MOG) gene polymorphism is not associated with migraine diseases in the Turkish population - Etem, Ebru Onalan; Berilgen, Said; Ozel, Seda; Elyas, Halit; Mungen, Bulent (Elsevier Sci Ltd, 2011)
[Abstract Not Available]
European Biotechnology Congress -- SEP 28-OCT 01, 2011 -- Istanbul, TURKEY